2020
DOI: 10.3390/ijms21249751
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Lysyl Oxidase Family Members in the Tumor Microenvironment and Progression of Liver Cancer

Abstract: The lysyl oxidase (LOX) family members are secreted copper-dependent amine oxidases, comprised of five paralogues: LOX and LOX-like l-4 (LOXL1-4), which are characterized by catalytic activity contributing to the remodeling of the cross-linking of the structural extracellular matrix (ECM). ECM remodeling plays a key role in the angiogenesis surrounding tumors, whereby a corrupt tumor microenvironment (TME) takes shape. Primary liver cancer includes hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 111 publications
(174 reference statements)
4
35
0
Order By: Relevance
“…There are increasing reports demonstrating the promising effect of targeting hypoxia-responsive genes, such as LOX , LOXL2 , and VEGFA . For instance, a couple of drugs targeting LOX family members are in the early stage of clinical trials [ 5 ], including pancreatic and colorectal adenocarcinoma [ 10 , 11 ]. Sorafenib was shown to hit the first breakthrough systemic therapy for treating advanced HCC via disrupting VEGF signaling [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are increasing reports demonstrating the promising effect of targeting hypoxia-responsive genes, such as LOX , LOXL2 , and VEGFA . For instance, a couple of drugs targeting LOX family members are in the early stage of clinical trials [ 5 ], including pancreatic and colorectal adenocarcinoma [ 10 , 11 ]. Sorafenib was shown to hit the first breakthrough systemic therapy for treating advanced HCC via disrupting VEGF signaling [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lysyl oxidase family members are secreted copper-dependent oxidases, including five paralogues: LOX , LOX -like 1–4 ( LOXL 1–4), which act to exert catalytic activity to remodel the cross-linking of the extracellular matrix (ECM) of fibrotic liver and that of a corrupted tumor microenvironment (TME) [ 4 ]. To date, the roles of LOX and LOXL 2 in the clinical significance and therapeutic implication of HCC are mostly studied as compared to the other family members [ 5 ]. The fact that LOX and LOXL 2 serving as critical factors in mediating the formation of a corrupted TME and promoting the progression of metastasis of HCC through activating pathways involved in hypoxia responsive signaling and angiogenesis, and epithelial mesenchymal transition (EMT) has been highlighted [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a remodeled, stiff ECM can support angiogenesis with abnormal vasculature, leading to a corrupt TME which promotes tumor dissemination [74]. In this regard, the function of lysyl oxidase (LOX) family members on a pro-tumoral TME of HCC by remodeling the ECM was recently noted [75]. More notably, Wong et al demonstrated that miR-29a acts as a negative regulator on lysyl oxidase like 2 (LOXL2) through interacting with the 3'UTR, thereby impeding the HCC metastasis [64].…”
Section: Fibrosismentioning
confidence: 99%